Management of Congenital Midline Nasofrontal Masses: Case Report and Review of Literature - A. C. Volck; G. A. Suárez; A. J. Tasman (Case Reports in Otolaryngology)
Epidermoid cysts, dermoids, gliomas, and meningo-/encephaloceles are the most important differential diagnoses in congenital nasofrontal masses. Since they arise from an abnormal fusion during fetal development, intracranial extension of the lesion has to be ruled out radiologically before therapy. Dermoids are the most common entity. We report about a congenital epidermoid cyst of the glabella and nasion that had been growing over the last two years before presentation in a 24-year-old patient. We discuss radiological imaging and the different surgical approaches described in literature.